N‐Octanoyl dopamine transiently inhibits T cell proliferation via G1 cell‐cycle arrest and inhibition of redox‐dependent transcription factors. Issue 3 (13th June 2014) - Wedel, Johannes; Hottenrott, Maximillia C.; Stamellou, Eleni; Breedijk, Annette; Tsagogiorgas, Charalambos; Hillebrands, Jan‐Luuk; Yard, Benito A.
Abstract : N‐octanoyl dopamine displays transient T cell suppressive activity by preventing NFκB and AP‐1 activation, and acts synergistically with calcineurin inhibitors on T cell proliferation. Abstract : Recently, we developed a nonhemodynamic dopamine derivative, NOD, which has profound anti‐inflammatory effects in vitro. As NOD also protects rats from ischemic AKI, the present study tested whether NOD is able to modulate cellular immunity for potential use as a T cell‐suppressive agent. To this end, T cells were stimulated by anti‐CD3/CD28 or PMA/ionomycin in the presence or absence of different concentrations of NOD. T cell proliferation, activation markers, intracellular cytokine expression, and activation of transcription factors were assessed. Whereas T cell proliferation was inhibited significantly by NOD at Day 3, proliferation was restored at Day 7 or later depending on the NOD concentration used. Inhibition of proliferation was reflected by a diminished CD25 expression and switch from naive to memory T cells. Early TCR activation events were unaffected, yet NF‐κB and AP‐1 were strongly inhibited by NOD. The inhibitory effect of NOD seemed to be dependent on its redox activity, as NOT, a redox‐inactive NOD derivate, did not influence proliferation. NOD displayed synergistic effects with CNIs on T cell proliferation. Our data demonstrate that NOD displays T cell‐suppressive activity. In keeping with its anti‐inflammatory action and its beneficial effect on ischemia‐induced AKI, NOD may be an interesting drug candidate to prevent CNI‐related side‐effects.